2008
DOI: 10.1038/bmt.2008.155
|View full text |Cite
|
Sign up to set email alerts
|

Lack of utility of chimerism studies obtained 2–3 months after myeloablative hematopoietic cell transplantation for ALL

Abstract: Lineage specific chimerism studies are commonly obtained at several time points after nonmyeloablative haematopoietic cell transplantation to assess the tempo and degree of engraftment, and to monitor graft rejection. For patients who receive myeloablative transplants, the value of frequent chimerism analyses using sensitive molecular techniques is less certain. In this study, a retrospective analysis was performed to assess the transplant outcome of 89 adult patients with acute lymphocytic leukaemia who had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 11 publications
5
21
0
Order By: Relevance
“…The 2001 workshop of the American Society of Blood and Marrow Transplantation and the International Bone Marrow Transplant Registry recommended against the routine assessment of chimerism in this group of patients. 1 Some recent studies have confirmed these findings and recommendations; 4,5 however, a recent report found that 28% of patients showed mixed chimerism at day 90 following MA HSCT, and these patients had worse outcomes than those with complete chimerism. The authors concluded that the detection of mixed chimerism following MA HSCT should prompt clinical intervention.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…The 2001 workshop of the American Society of Blood and Marrow Transplantation and the International Bone Marrow Transplant Registry recommended against the routine assessment of chimerism in this group of patients. 1 Some recent studies have confirmed these findings and recommendations; 4,5 however, a recent report found that 28% of patients showed mixed chimerism at day 90 following MA HSCT, and these patients had worse outcomes than those with complete chimerism. The authors concluded that the detection of mixed chimerism following MA HSCT should prompt clinical intervention.…”
Section: Introductionmentioning
confidence: 58%
“…The results reported here are similar to those reported by others. [2][3][4][5][6][7][12][13][14] These data undermine the use of the terms 'myeloablative' and 'nonmyeloablative'. As Deeg 15 has recently pointed out, all transplantations in patients with malignant hematological disorders are designed to be myeloablative in order to achieve disease eradication.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite its diagnostic potential, it is not established as a routine parameter after RIC. The relevance of subset-specific chimerism testing after MA conditioning regimens has been discussed controversially, 5,12,20,27 and studies in pediatric patients are scarce. 1,15,16,18 The ultimate objective of chimerism analysis in the context of graft rejection is to identify impending graft loss as soon as possible to permit timely onset of therapeutic interventions to stabilize the graft, such as reducing immunosuppressive drugs or applying targeted donor leukocyte infusions (DLI).…”
Section: Introductionmentioning
confidence: 99%
“…5,6,[15][16][17][18] The plethora of different schedules and technical approaches to the detection and monitoring of chimerism renders the comparison of published data on the utility of chimerism testing for the prediction of graft rejection difficult. 6,8,[15][16][17][19][20][21][22] Moreover, the significance of different leukocyte subsets for graft rejection does not necessarily correlate with their relative and absolute levels due to their distinct immunological properties. In a number of studies, analysis of chimerism in purified leukocyte fractions was shown to be more informative than testing total leukocytes.…”
Section: Introductionmentioning
confidence: 99%